Eco-biological Study of the Mosquitofish Gambusia affinis from Oubeira lake - Chalabia Chabet Dis; Fatma Zohra Toumi Kara; Saida Bouamama; Fayrouz Sahra; Mohamed Amine Boucena (Department of Aquaculture, 2022)
Gambusia was studied in Oubeira lake in spring 2016. A total of 100 specimens were collected in the lake. The sex ratio was F:M = 5.12: 1. The length-weight relationship was estimated for the population, with Wt = 0.0197Lt2.4451. The condition factor was calculated C=1±0.2 (for population) and a significant difference was observed between males and females. For 100 examined stomachs, the diet mainly consists of algae (N=54.96%, Pi= 166%, O=91%), followed by the mosquito larvae (N=21.52%, Pi= 65%, O=49%), detritus (N=19.2%, Pi= 58%, O=46%) and arthropods (N=4.3%, Pi= 13%, O=13%). For mosquitoes, two genus were recorded: Culiseta and Culex with 4 species: Culex pipiens, Culex theileri, Culex laticinctus and Culex antennatus. The culture experiments confirmed the important predation on mosquito larvae was observed with feeding intensity for females and males of 86 ± 12.28 % and 92 ± 8 % for the Culex larvae and 91 ± 7 and 93.66 ± 5.68 for the Culiseta larvae, respectively. No significant difference was observed between the sexes or for mosquito larvae. Our data support the idea that the introduction of mosquitofish has both negative and positive effects since this fish feeds on the most abundant food and not only on mosquitoes.